1988
DOI: 10.1002/bjs.1800750407
|View full text |Cite
|
Sign up to set email alerts
|

Risk to surgeons: A survey of accidental injuries during operations

Abstract: A survey was conducted with the participation of eight consultant general surgeons, two consultant urologists, four consultant orthopaedic surgeons and four surgical residents to find the incidence of accidental injuries to surgeons and their assistants during operations. Of the total of 2016 operations over a one year period there were 112 reported accidental injuries. These included 107 needle stick injuries, 4 knife cuts and 1 diathermy burn. We found that accidental injuries to surgeons during operations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(34 citation statements)
references
References 5 publications
0
32
0
2
Order By: Relevance
“…This is similar to results from the previous study and various earlier studies. 10,17,18 Momah,13 in her study of two hospitals, where she followed doctors and nurses for two three-monthly periods to ascertain the occurrence of injuries, found the incidence rates of needle stick and sharp injuries to be 3.9ppy and 2.2ppy for the first and second quarters respectively. A study among health workers in teaching hospitals in Taiwan found the incidence of needle prick to be 1.30ppy and 1.21ppy for other sharp objects.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to results from the previous study and various earlier studies. 10,17,18 Momah,13 in her study of two hospitals, where she followed doctors and nurses for two three-monthly periods to ascertain the occurrence of injuries, found the incidence rates of needle stick and sharp injuries to be 3.9ppy and 2.2ppy for the first and second quarters respectively. A study among health workers in teaching hospitals in Taiwan found the incidence of needle prick to be 1.30ppy and 1.21ppy for other sharp objects.…”
Section: Discussionmentioning
confidence: 99%
“…Perforations in the scrub nurses' group appear to be related to the handling of instruments and needles, irrespective of the procedure being carried out [73]. In a comparative study, it has been shown that the highest incidence of glove perforations occurred among general surgeons in comparison to other specialties such as orthopedics and urology [74].…”
Section: Glove Perforationmentioning
confidence: 99%
“…The potential for infection by human immunodeficiency virus (HIV) or hepatitis (B and C) through contact with a patient's blood is well recognized, 5e7 and the risk of transmission of diseases via the conjunctiva and cornea has been reported. 8,9 Various authors have calculated the cumulative risk of acquiring occupationally transmitted HIV to vary from 1% to 10%. 10e12 Simonian et al 13 found that 4.5% of patients undergoing elective orthopaedic surgery were infected with hepatitis C virus over a one-year period.…”
Section: Discussionmentioning
confidence: 99%